2021
DOI: 10.3390/nu13051413
|View full text |Cite
|
Sign up to set email alerts
|

Individuals Diagnosed with Binge-Eating Disorder Have DNA Hypomethylated Sites in Genes of the Metabolic System: A Pilot Study

Abstract: Binge-eating disorder, recently accepted as a diagnostic category, is differentiated from bulimia nervosa in that the former shows the presence of binge-eating episodes and the absence of compensatory behavior. Epigenetics is a conjunct of mechanisms (like DNA methylation) that regulate gene expression, which are dependent on environmental changes. Analysis of DNA methylation in eating disorders shows that it is reduced. The present study aimed to analyze the genome-wide DNA methylation differences between ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 82 publications
(86 reference statements)
0
2
0
1
Order By: Relevance
“…Ancak 2021 Nisan ayında yayınlananbir çalışma, 21 TYB ve 25 BN tanısı alan bireyler arasındaki genom çapında DNA metilasyon farklılıklarını analiz etmiş. Sonuç olarak TYB ve BN'li bireyler arasında genom çapında, önemli 11 farklı DNA metilasyon bölgesi tespit etmişler ayrıca TYB olan olguların metabolik fonksiyonlarla ilgili olan ST3GAL4, PRKAG2 ve FRK genlerinde hipomentilasyona rastlarken BN'li olgularda ise böyle bir sonuç elde etmemişlerdir (65).…”
Section: Yb'de Dna Metilasyonu üZerine Bulgularunclassified
“…Ancak 2021 Nisan ayında yayınlananbir çalışma, 21 TYB ve 25 BN tanısı alan bireyler arasındaki genom çapında DNA metilasyon farklılıklarını analiz etmiş. Sonuç olarak TYB ve BN'li bireyler arasında genom çapında, önemli 11 farklı DNA metilasyon bölgesi tespit etmişler ayrıca TYB olan olguların metabolik fonksiyonlarla ilgili olan ST3GAL4, PRKAG2 ve FRK genlerinde hipomentilasyona rastlarken BN'li olgularda ise böyle bir sonuç elde etmemişlerdir (65).…”
Section: Yb'de Dna Metilasyonu üZerine Bulgularunclassified
“…Interestingly, two recent studies reported differential levels of DNA methylation in several sites of the OXTR gene in female patients with AN as compared to females remitted from AN and healthy females, and DNA methylation was correlated with markers of AN severity [ 13 , 26 ]. However, only two studies so far investigated epigenetic alterations in patients with binge eating, but the OXTR was not included, and samples were heterogeneous [ 28 , 29 ] and small (< 30 cases) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, genetic associations between ED and substance use have been described [ 6 ]. Additionally, the genetic-environment relationship in ED has been studied through DNA methylation, reporting perturbations in the methylation levels of some genes ( DRD2 , SLC6A3 , POMC , OXTR , among others) [ 2 , 7 , 8 ]. However, genes do not function alone: on average, each gene is estimated to interact with another four or eight genes, and to be involved with 10 biological functions.…”
Section: Introductionmentioning
confidence: 99%